Aquatic insect functional traits indicate spatiotemporal changes in potential aquatic prey availability to terrestrial consumers after small dam removal - Peter E. Carlson (Journal of Freshwater Ecology)
As a restoration measure, dam removal is expected to lead to ecological improvement. However, there is little understanding how dam removal affects lateral interactions across ecosystem boundaries. The transfer of aquatic resource subsidies into terrestrial food webs via the winged adult stages of aquatic insects is recognized as a key component in the functioning of riverine networks. Here, a quantitative review was performed to investigate the potential of dam removal to restore lateral connectivity with riparian ecosystems in terms of the production and dispersal of aquatic insect subsidies. Specifically, the functional trait composition of benthic invertebrate insect assemblages was analyzed to assess how the dispersal and life history of stream invertebrates are affected by dam removal. Functional trait responses to dam removal were quantified within the downstream, impoundment and upstream sections, utilizing extracted or calculated functional traits from a comprehensive search of empirical studies containing pre- and post-dam removal data along with the specific sampling distance from the dam (downstream and impoundment) or distance from the impoundment (upstream) and time from dam removal. The findings of this study suggest that the removal of small dams results in a more constant, rather than pulsed, supply of aquatic insects as resource subsidies for terrestrial consumers. Furthermore, results indicate an increase in potential aquatic prey dispersal extent into the terrestrial landscape in the downstream section and initially in the impoundment.